Variación de ingresos del Agroquímico ‘‘Agrozam’’ ubicado en la parroquia La Unión durante el periodo 2020-2021. - Velasco Uca, Angelica Jazmin (2023)
The present case study based on the Variation of income of "Agrozam" during the periods 2020 - 2021, in which the problem revolves around the variation or decrease in income caused by the reduction in sales during the period 2021, in where the company saw the need to make changes in sales prices and in the planning of its activities so that the company does not suffer serious problems in the future that have no solutions. Through this case study, it is intended to analyze the causes that caused the variation in the company's income. A mixed methodology was also applied, that is, the quantitative and qualitative method was used, which were used together and allowed the collection of information and, at the same time, a detailed analysis of each value obtained by applying formulas specifically for financial indicators. The analysis of the results of the variations obtained are of the utmost importance for the company, thanks to them it is possible to know the real economic situation of Agrozam and, in turn, to be able to use new methods that help to solve problems every time they arise. Finally, carried out the investigation to carry out this case study, it was possible to conclude that, during the 2021 period, Agrozam had a lower solvency capacity to supply the needs of the company, certain operational processes being affected.